The demand for reinsurance: Empirical test for the UK life insurance industry - fan, xue (2008)
This study is conducted aiming to test for the determinants of the demand for reinsurance. Three new variables, say new business, lines of business and group status are created in this study to test for their impact on life insurers demand for reinsurance. Apart from that, five control variables are also included in this study (firm size, financial strength, business concentration, profitability and organizational form). Tests are performed using data from all the 291 operating UK life insurers for the time period from 1995 to 2007. The data for 2005 to 2007 include information on intra-group reinsurance and external reinsurance. The results for this study indicate that new business has a significant effect on life insurers reinsurance demand, and for life insurers with a large proportion of with-profit insurance business and belonging to a group, their demand for reinsurance, especially intra-group reinsurance is stronger than others. This study also provides evidence on the impact of firm size, financial strength and organizational form, indicating that small proprietary life insurers with pool financial position would demand for reinsurance more than others. For business concentration and profitability, the result for this study is quite weak.